An improvement of the computational effective diameter measurement in thoracic computed tomography examinations - Choirul Anam; Riska Amilia; Wahyu S. Budi; Heri Sutanto; Zaenul Muhlisin; Ariij Naufal; Geoff Dougherty (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
A method to calculate a corrected effective diameter (DMIL) to more accurately estimate the dose received by a patient in chest computed tomography (CT) examination had been previously proposed. However, the discrepancy between DMIL and water-equivalent diameter (Dw) is still relatively high (i.e. about 6%). Furthermore, the method is still performed manually, so it is laborious and time-consuming. This study aims to improve the corrected effective diameter with bone correction (Deffcorr) and to automatically calculate it. The automated Deffcorr was calculated as the square root of the product of these corrected AP and LAT diameters. The approach was implemented on 30 patients who had undergone chest CT examination with the standard protocol. The results show that the correlation between the Deffcorr and Dw is R2=0.93 with no statistical difference (p>0.05). The automated Deffcorr is 3.1% lower than Dw. While the DMIL is 10.5% higher than Dw and both are statistically different (p<0.05). In conclusion, the new Deffcorr was introduced and the result obtained was closer to Dw than DMIL. This method is simple enough to be used as an alternative method to accurately estimate Dw for radiation dose estimation in clinical chest CT scanning.